The features of psychological response to the disease in cancer patients - Мухаровська, Інна Романівна (ScienceRise: Medical Science, 2016)
The aim of research was to reveal the features of psychological response to the disease in cancer patients at the different stages of treating process and depending on sex. Materials and methods. The research was carried out on the base of Kyiv city cancer center during 2014 – 2016. 80 cancer patients were examined at diagnostic stage, at the stage of final confirmation of diagnosis and the choice of the therapy methods– G(d), 187 persons, who underwent the anti-tumor treatment for the first time– G(п), and 155 cancer patients, who needed the repeated treatment as a result of the progressing or relapse of disease – G(в). The questionnaire “The types of attitude to disease” was used as a diagnostic instrument. Results. In 62,8% of cancer patients were revealed the non-adaptive types of response to the disease, 16,6% had combined forms of response, including personal and interpersonal maladjustment, the disorder of intra-psychical adaptation prevailed over inter-psychical one. The progressing of cancer disease conditioned the complication of manifestations of response to the disease by the way of junction of non-adaptive types and creation of their mixed forms, intensification of anxious, hypochondriac, melancholic, apathetic, paranoiac, dysphoric components in the composition of psychic response. Among cancer patients the most often were anosognostic (13,0%), anxious-sensitive (11,4%), ergopathic-anxious (10,4%), sensitive (7,8%), anxious (7,6%) and hypochondriac types (6,4%). The differences in the structure and frequency of occurrences of the types of responses to the disease indicated the presence of gender features of psychical response. Conclusion. The determination and correction of non-adaptive forms of the response to disease is an important part of medical-psychological help for the cancer patients